The use of card sort media to overcome boredom in learning islamic cultural history - Zazali Juwita; Intan Najma Pratiwi; Yolanda Mardianti; Muhammad Agustian Ruyansyah; Muhammad Taufiqurrahman; Himad Ali (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
SKI learning in Madrasah tends to be rote and merely informative. Thus, students often experience boredom when learning SKI. Saturation can be interpreted as boredom. This boredom causes students to have difficulty in understanding SKI learning material. To overcome this boredom, one way is to use innovative learning media such as card sort. Card sort media is proposed as a solution to overcome problems in SKI learning. This research uses literature study method as the main approach in data collection and analysis. The results show that card sort media can make learning more interactive and interesting, so it can increase students' enthusiasm and motivation to learn. However, the drawback is that it can take a lot of time to prepare. Then it will be easy for noise to occur if the teacher cannot condition the class properly. In addition, card sort media can only be used for group learning and there is a possibility of deviating students' attention, especially if there is an answer that attracts their attention. As for its use, card sort media can only be used on certain materials. So, not all learning materials can be used in card sort media.